Protecting directors and officers against liability arising from aggressive earnings management - Boyer, Martin; Hanon, Amandine (Assurances et gestion des risques / Insurance and Risk Management, 2009)
A lingering topic in corporate governance is whether corporate directors should be protected against shareholder lawsuits and whether such protection reduces the incentives of directors to monitor appropriately the behaviour of corporate officers. To achieve this goal, we examine whether corporations whose corporate managers’ wealth is protected under a directors’ and officers’ liability insurance policy (D&O insurance hereafter) are more to report accounting results aggressively. Using discretionary accruals as our measure of accounting aggressiveness, the results in our paper suggest that the magnitude of discretionary accruals has no real impact on the demand for D&O insurance, be it on the decision to purchase insurance or on the amount of limit chosen. The positivity of discretionary accruals appears, however, to have an impact on the decision to purchase insurance. Surprisingly, although these insurance policies protect directors and officers in the event they make a “mistake” in their role as representatives of the company, directors do not seem to see this as an invitation to be a little less careful when overseeing the firm’s accounting practices.